Identification, characterization, and immunogenicity of the lactoferrin-binding protein from Helicobacter pylori. - Dhaenens, L (1997)
Iron acquisition plays an important role in bacterial virulence. Different studies have been initiated to define the mechanism by which Helicobacter pylori acquires iron. We had previously demonstrated that human lactoferrin (HLf) supported full growth of the bacteria in media lacking other iron sources. The ability of H. pylori to use HLf as an iron source had been found to be dependent on cell-to-protein contact. Since lactoferrin has been found in significant amounts in human stomach resection specimens from patients with superficial or atrophic gastritis, the iron uptake of H. pylori via a specific HLf receptor may play a major role in the virulence of H. pylori infection. In this study, by using affinity chromatography with biotinylated HLf and streptavidin-agarose, we identified a 70-kDa lactoferrin-binding protein (Lbp) from outer membrane proteins of H. pylori. This Lbp was only present when H. pylori was grown in an iron-starved medium, suggesting that it serves in iron uptake. Direct binding assays with increasing concentrations of biotinylated HLf demonstrated that the lactoferrin interaction with the outer membrane of H. pylori grown in iron-restricted medium was saturable. Competitive binding experiments with bovine and human lactoferrin and with transferrin of horse, bovine, and human origin indicated that this Lbp appeared highly specific for HLf. A number of other studies have focused on the importance of transferrin and lactoferrin receptors in pathogenic bacteria and their specificity with the host species. This observation might explain the very strict human specificity of H. pylori.